Double-exclusive liquid repellency (double-ELR): an enabling technology for rare phenotype analysis. Issue 18 (2nd August 2018) - Li, Chao; Yu, Jiaquan; Paine, Paxton; Juang, Duane S.; Berry, Scott M.; Beebe, David J.
Abstract : Complex cell-culture microenvironments with both spatial and temporal resolutions are enabled by double-exclusive liquid repellency and underoil sweep patterning. Abstract : Double-exclusive liquid repellency (double-ELR) is an extreme wettability phenomenon in which adjacent regions selectively and completely repel immiscible liquids with different surface chemistries on a non-textured substrate ( i.e., a substrate in absence of micro/nano-structures). Under double-ELR conditions, each liquid exhibits no physical contact (contact angle of 180°) with its non-preferred surface chemistry, thus enabling complete partitioning of adjacent fluidic volumes ( e.g., between water and oil). This enables a new type of cell culture-based assay, where cell loss from common failure modes ( e.g., biofouling from inadvertent cell adhesion, detrimental moisture loss/gain, and liquid handling dead volumes) is significantly mitigated. Importantly, the principles of double-ELR were leveraged to achieve underoil sweep patterning, a no-loss, robust and high-throughput distribution of sub-microliter volumes of aqueous media (and cells). In addition to high-efficiency distribution via sweep patterning, double-ELR can be used to construct "modular" ( i.e., easily implemented and/or linked together with spatial and temporal control) higher-order architectures for in vitro imitation of physiologically relevant microenvironments that are of particular interest within the cell assay community, including multi-phenotype cultures with excellent spatial and temporal control, three-dimensional layered multi-phenotype cultures, cultures with selective mechanical cues of extracellular matrix ( i.e., collagen fiber alignment), and spheroid cultures. Together, these features of double-ELR uniquely facilitate culture and high content analysis of limited cellular samples ( e.g., a few hundred to a few thousand cells).